Increase of angiotensin II type 1 receptor auto-antibodies in Huntington's disease - Lee, De-Hyung; Heidecke, Harald; Schroeder, Alexandra; Paul, Friedemann; Wachter, Rolf; Hoffmann, Rainer; Ellrichmann, Gisa; Dragun, Duska; Waschbisch, Anne; Stegbauer, Johannes; Klotz, Peter; Gold, Ralf; et al. (Molecular Neurodegeneration, 2014)
In the recent years, a role of the immune system in Huntington's disease (HD) is increasingly recognized. Here we investigate the presence of T cell activating auto-antibodies against angiotensin II type 1 receptors (AT1R) in all stages of the disease as compared to healthy controls and patients suffering from multiple sclerosis (MS) as a prototype neurologic autoimmune disease.As compared to controls, MS patients show higher titers of anti-AT1R antibodies, especially in individuals with active disease. In HD, anti-AT1R antibodies are more frequent than in healthy controls or even MS and occur in 37.9% of patients with relevant titers >= 20 U/ml. In a correlation analysis with clinical parameters, the presence of AT1R antibodies in the sera of HD individuals inversely correlated with the age of onset and positively with the disease burden score as well as with smoking and infection.These data suggest a dysfunction of the adaptive immune system in HD which may be triggered by different stimuli including autoimmune responses, infection and possibly also smoking.
EVALuna2:22303